A scoping review of personal librarian programs in academic libraries. Issue 1 (15th August 2022) - Murphy, James E.; Premji, Zahra; Jones, Rhiannon
Abstract: Personal librarian programs have been used in academic libraries since 1984, peaking in prevalence in the 2010s, and although assessment varies, they have shown to be a successful student engagement program in academic libraries. To survey and compile these programs for future program development, the authors comprehensively reviewed published literature on academic library programs categorized as personal librarian programs using scoping review methodology. Sources searched were Academic Search Complete, Web of Science core collection, Library and Information Science Abstracts, Library and Information Science Sources, Education Research Complete, monographs, conference proceedings, and gray literature. Programs were primarily in North America, with eighteen in the U.S., four in Canada and one in South Africa. The authors found that a plan of assessment should be in place before embarking on a personal librarian program. By reviewing the various models of personal librarian programs, the authors hope that this scoping review will assist librarians in selecting the appropriate model for their academic institution.